2005
DOI: 10.1111/j.1468-0343.2005.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Accountability and Corruption: Political Institutions Matter

Abstract: This study uses a cross-country panel to examine the determinants of corruption, paying particular attention to political institutions that increase accountability. Even though the theoretical literature has stressed the importance of political institutions in determining corruption, the empirical literature is relatively scarce. Our results confirm the role of political institutions in determining the prevalence of corruption. Democracies, parliamentary systems, political stability, and freedom of press are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
170
4
23

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(216 citation statements)
references
References 38 publications
(55 reference statements)
6
170
4
23
Order By: Relevance
“…So increase in press freedom has reduced the level of corruption. These empirical findings are supported by the previous findings of Lederman et al (2005) and Brunetti-Weder (2003). The value of R-square is 0.13, which shows that only 13% variation in the level of corruption is explained by non-economic factors.…”
Section: Empirical Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…So increase in press freedom has reduced the level of corruption. These empirical findings are supported by the previous findings of Lederman et al (2005) and Brunetti-Weder (2003). The value of R-square is 0.13, which shows that only 13% variation in the level of corruption is explained by non-economic factors.…”
Section: Empirical Findingssupporting
confidence: 88%
“…Empirically this issue was tested by Lederman et al (2005) and Brunetti-Weder (2003), and they found that higher degree of press freedom will lead to reduction in the level of corruption. To see the relationship between these two in developing countries, we have formulated the following hypothesis:…”
Section: Hypothesis Derivationmentioning
confidence: 99%
“…The largest bribes were paid to the television media, followed by bribes to politicians and judges. Lederman et al (2005) also found similarly beneficial outcomes correlating with the levels of freedom provided the press in society.…”
Section: Literature Reviewmentioning
confidence: 57%
“…Costas et al (2011), Freille et al (2007), Lederman et al (2005), Adsera et al (2003), Brunetti and Weder (2003), and Besley and Burgess (2002) provide evidence on the importance of a free press in reducing corruption. However, as Johnson et al (2011), Chang et al (2010), and Golden (2006) point out, corruption exists even in advanced democracies.…”
Section: Introductionmentioning
confidence: 99%
“…Corrupt incumbents may lose votes but not enough to deny them re-election, as long as they keep the level of corruption in check and do not allow it to damage overall economic performance significantly. This would explain why Pellegrini and Gerlagh (2008) and Lederman et al (2005) find the level of corruption to be lower, and Drury et al (2006), its harm on economic growth to be less, in democratic countries.…”
Section: Introductionmentioning
confidence: 99%